Prostatic Hyperplasia And Homoeopathy:An Evidence Based Case Report. - R Shah, Puneet; Modiyani, Neha; Chaudhary, Himani; Jhanginia, Meenakshi; Kumar Meena, Rajesh; Mathur, Astha; Bhradwaj, Daisy (Journal of Neonatal Surgery, 2025)
Benign Prostatic Hyperplasia is an age associated prostate gland enlargement that can cause difficulty in urination. It is one of the most common disease in ageing men and the most common cause of lower urinary tract symptoms. A case of 67 years old male reported with a condition of Benign Prostatic Hyperplasia along with the pain during micturition with increase frequency of urine at night and occasionally retention of urine was present. The ultrasound report of patient shows the volume of prostate was 37 cc. During the line of treatment, he was given Tabaccum 30 thrice a day and SabalserrualataQ twice a day repeatedly for 6 months of time period. During this time period, his urinary complaints were getting better and after five months of treatment, ultrasound report shows the volume of prostate reduced to20cc. Patient is having relief in urinary complaints and frequency of urine decreases, his pain in abdomen is also better. So this case shows the effectiveness of homeopathic medicines in cases where other line of treatment are not more feasible.